Improving fitness of elite handball players: Small-sided games vs. high-intensity intermittent training - Iacono, A. D.; Eliakim, A.; Meckel, Y. (The Journal of Strength and Conditioning Research, 2015)
The present study was designed to compare the effects of high-intensity intermittent training (HIIT) and small-sided games (SSGs) training on fitness variables of elite handball players. Eighteen highly trained players (mean age ± SD: 25.6 ± 0.5 years) were assigned to either HIIT or SSGs group training protocols twice per week for 8 weeks. The HIIT consisted of 12-24 × 15 seconds of high-intensity runs interspersed by 15 seconds of recovery. The SSGs training consisted of 3 against 3 small-sided handball games. Both training methods were matched for exercise duration and recovery at each training session. Before and after 8-week training, the following fitness variables were assessed—speed: 10- and 20-m sprint time, agility: handball agility specific test (HAST), upper arm strength: 1 repetition maximum (1RM) bench press test, lower limb power: counter-movement jump tests with (CMJarm) and without (CMJ) arm movement, and aerobic fitness (yo-yo intermittent recovery test level 1 [YYIRTL1]). Significant improvement was found in the YYIRTL1 (23.3 and 26.3%, respectively), 10-m sprint (2.3 and 4.1%, respectively) and 20-m sprint (2.1 and 4%, respectively), HAST (1.1 and 2.2%, respectively), 1RM bench press (6.8 and 12.3%, respectively), CMJ (7.4 and 10.8%, respectively), and CMJarm (6.4 and 8.9%, respectively) following training in both groups (p = 0.05 for all). There was a significantly greater improvement in 10- and 20-m sprint, HAST, 1RM, CMJ, and CMJarm following the SSGs training compared with the HIIT (p = 0.05 for all). These results indicated that both HIIT and SSGs are effective training methods for fitness development among elite adult handball players. However, SSGs training may be considered as the preferred training regimen for improving handball-specific fitness variables during the in-season period.